Holocene glacier variations in the Terra Nova Bay area (Victoria Land, Antarctica) - BARONI, CARLO; OROMBELLI G. (Antarctic Science, 1994)
Information on Holocene glacier variations in Antarctica is limited and sometimes contradictory. However, if the behaviour of the glaciers during the recent past can be clarified, their sensitivity to climatic changes can be evaluated and their contribution to the sea levelvariation may be predicted. Through the study of local glaciers and floating ice shelves in the Terra Nova Bay area, new information has been gathered. Between 7500 and 5000 yr B.P., after the glacial retreat which followed the Last Glacial Maximum, the Nansen Ice Sheet and the Hells Gate ice shelf were a few kilometres less extensive than they are now. During the second half of the Holocene, both the local glaciers and the ice shelves advanced to positions that were more extensive than their present ones, although not all the variations are adequately dated. A retreat phase of the Edmonson Point glacier occurred during late Middle Ages between 920-1050 A.D. and 1270-1400 A.D. as documented by ten 14C dates obtained from shells in ice-cored moraines. A subsequent advance occurred after the 15th century in a period corresponding to the Little Ice Age.